A novel impedance sensing approach for precise electromechanical characterization of cells. (27th August 2019) - Mahesh, Karthik; Varma, Manoj M; Sen, Prosenjit
Abstract: In this paper, we demonstrate a microfluidic impedance spectroscopy platform that simultaneously probes two important biophysical parameters of cells—one, their electrical properties and two, their mechanical properties. Instead of using a high-speed camera for estimation of mechanical properties (deformability) of cells, we present a new design where deformability is estimated using the time difference (transit time) between the generation of electrical signals. The concept was validated using chemically stiffened erythrocytes. The presented design also involves a novel flow correction technique that was developed to negate the errors arising from flow rate fluctuations in such devices, resulting in rapid and error-free data acquisition. Using this platform, we further investigate changes in deformability and cellular properties of lymphocytes in diabetic patients by comparing them with healthy volunteers. Results from testing >9000 cells in each population suggest significant changes in properties of diabetic lymphocytes.